Rakova Jelša and Sibirija - ethnic neighborhoods in transformation - Rebernik, Dejan (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2015)
Rakova Jelša and Sibirija are the only two neighborhoods in Ljubljana with a majority of non Slovene population. They were formed with immigration from the former Yugo slavia since 1970s. This immigration to Slovenia and Ljubljana and correspondent deve lopment of ethnic neighborhoods Rakova Jelša and Sibirija are presented in the paper. Basic socioeconomic characteristics of both neighborhoods are analyzed on the basis of census data from 1981 to 2011. With the survey of local population we tried to evaluate the satisfaction with the quality of the living environment and analyzed the issue of inte gration of immigrants into the new environment.
Keywords: etnična struktura; geografija naselij; Ljubljana; mesta; mestne četrti; priseljevanje; Rakova Jelša; Sibirija